Parent-Adolescent Communication On Reproductive Health and Sexual Of Adolescent - Febriana, Annisa; Mulyono, Sigit (Jurnal Keperawatan, 2019)
ABSTRACTIntroduction: In adolescence, there are various changes, both physical, cognitive, and social, which cause adolescents vulnerable to reproductive health problems. The family as the closest part of adolescence is one of the main factors in improving adolescent reproductive health and has a very important role in providing sexual and reproductive health information to adolescents. Objective: to find out the communication between parents and teenagers about sexual and reproductive health. Method: The design used is a systematic review. Journal searches are conducted on online databases such as PubMed, Elsevier, Science Direct, and Google Scholar. Journals, articles, and literature reviews were found using keywords parent-adolescent communication, sexual and reproductive health, adolescents. Results: A total of 7 journal articles selected from 28 articles showed that communication between parents and adolescents regarding reproductive and sexual health was very important to do. However, the implementation is still lacking due to various factors such as lack of parental knowledge, parents lacking in communication skills, the presence of shame, and cultural influences that consider reproductive and sexual health issues as taboo to be discussed with adolescents. Discussion: The communication of parents and adolescents regarding reproductive and sexual health has been widely investigated in various countries. Interventions are needed to improve the quality of communication between parents and adolescents through increasing the knowledge of parents of these adolescents.Â